Stevia and Stevioside Attenuate Liver Steatosis through PPARα-Mediated Lipophagy in db/db Mice Hepatocytes - Miey Park; Anshul Sharma; Hana Baek; Jin-Young Han; Junho Yu; Hae-Jeung Lee (MDPI AG, 2022)
Lipophagy, a type of autophagy that breaks down lipid droplets, is essential in the regulation of intracellular lipid accumulation and intracellular free fatty acid levels in numerous organisms and metabolic conditions. We investigated the effects of Stevia rebaudiana Bertoni (S), a low-calorie sweetener, and stevioside (SS) on hepatic steatosis and autophagy in hepatocytes, as well as in db/db mice. S and SS reduced the body and liver weight and levels of serum triglyceride, total cholesterol, and hepatic lipogenic proteins. In addition, S and SS increased the levels of fatty acid oxidase, peroxisome proliferator-activated receptor alpha (PPARα), and microtubule-associated protein light chain 3 B but decreased that of sequestosome 1 (p62) in the liver of db/db mice. Additionally, Beclin 1, lysosomal associated membrane protein 1, and phosphorylated adenosine monophosphate-activated protein kinase protein expression was augmented following S and SS treatment of db/db mice. Furthermore, the knockdown of PPARα blocked lipophagy in response to SS treatment in HepG2 cells. These outcomes indicate that PPARα-dependent lipophagy is involved in hepatic steatosis in the db/db mouse model and that SS, a PPARα agonist, represents a new therapeutic option for managing associated diseases.